A LITERATURE REVIEW ON Acinetobacter baumannii AND THE CHALLENGES: INSIGHTS INTO VARIOUS CLINICAL AND PATHOPHYSIOLOGICAL CONDITIONS WITH REFERENCE TO BIOFILM FORMATION. - Anwar, Md Sahil; Biswas, Priyanka Paul; Sen, Aninda (Student’s Journal of Health Research Africa, 2024)
Acinetobacter baumannii is a Gram-negative multidrug-resistant pathogen that poses a significant threat to public health, particularly in healthcare settings. Its ability to resist desiccation, colonize abiotic surfaces, and form biofilms contributes to its persistence in medical environments. This literature review explores the various clinical and pathophysiological challenges posed by A. baumannii, with a focus on biofilm formation, surface motility, and virulence factors. The bacterial resistance to common antibiotics, including carbapenems, fluoroquinolones, and cephalosporins, exacerbates its role in nosocomial infections such as pneumonia, catheter-associated bacteremia, and soft tissue infections. Understanding the multifaceted nature of A. baumannii virulence can guide future therapeutic strategies aimed at mitigating its impact, particularly in critical care units. The review highlights the need for deeper investigations into virulence mechanisms, biofilm disruption strategies, and iron acquisition systems. Furthermore, it underscores the importance of enhancing infection control measures, improving antibiotic stewardship programs, and developing policies to reduce the incidence of multidrug-resistant infections. This synthesis serves as a guide for researchers, clinicians, and policymakers in addressing the challenges posed by AI. baumannii in clinical settings.